Impacts of corn and fed-cattle prices on price slides for feeder cattle - Kevin C. Dhuyvetter; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 2000)
Several important determinants need to be considered when analyzing price slides (priceweight relationships) for feeder cattle. The two most economically important determinants of price-weight slides are expected fed-cattle price and corn price. Price-weight slides increase notably when corn prices decline (i.e., the premium for light-weight calves increases as feed prices decrease). Likewise, when expected fed-cattle prices increase, price-weight slides increase. Knowing this information can help producers who forward contract feeder cattle, backgrounders making decisions regarding feeding calves to various weights, and producers making feeder cattle purchase decisions.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Price slides; Feeder cattle prices; Price determinants